Changes in the Th1 : Th2 Cytokine Bias in Pregnancy and the Effects of the Anti-Inflammatory Cyclopentenone Prostaglandin 15-Deoxy-Δ12, 14-Prostaglandin J2. (29th May 2012) - Sykes, Lynne; MacIntyre, David A.; Yap, Xiao J.; Ponnampalam, Sathana; Teoh, Tiong Ghee; Bennett, Phillip R.
Abstract : Pregnancy is a complex immunological state in which a bias towards T helper 2 (Th2) protects the fetus. Evidence suggests that proinflammatory cytokines increase the risk of poor neonatal outcome, independently of the direct effect of preterm labour. The anti-inflammatory prostaglandin 15-deoxy-Δ 12, 14 -Prostaglandin J2 (15dPGJ2 ) inhibits nuclear factor Kappa B (NF- κ B) in amniocytes and myocytes in vitro and is a ligand for the chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2) receptor. Here we examine the Th1:Th2 cytokine bias in pregnancy and whether 15dPGJ2 could be used to inhibit the production of the proinflammatory cytokines through inhibition of NF- κ B while simultaneously promoting Th2 interleukin 4 (IL-4) synthesis via CRTH2 in T helper cells. Peripheral blood mononuclear cells (PBMCs) from women at 28 weeks, term pre-labour, term labour as well as non-pregnant female controls were cultured with 15dPGJ2 or vehicle control and stimulated with phorbol myristyl acetate (PMA)/ionomycin. The percentage of CD4 + cells producing interferon gamma (IFN- γ ) and tumor necrosis factor alpha (TNF- α ) in response to PMA/ionomycin was significantly reduced in pregnancy. 15dPGJ2 reduced IFN- γ and TNF- α production in stimulated T helper cells, but did not alter IL-4 production in CRTH2 +ve cells. 15dPGJ2 also reduced phospho-p65 in stimulated PBMCs. In summary, 15dPGJ2 suppresses the Th1 response of PBMCs during pregnancy and active labour whilst maintaining the Th2 response suggesting a therapeutic benefit in reducing neonatal morbidity in inflammation-induced PTL.